The Political Costs of Taxation - Eva Davoine; Joseph Enguehard; Igor Kolesnikov (CESifo GmbH, 2025)
We examine the political costs of taxation in early modern France. We focus on efforts to enforce the salt tax, the rate of which varied across regions. Using a spatial difference-in-discontinuities design, we compare municipalities just inside the high-tax region with those just outside, before and after a reform aimed at curbing illicit salt smuggling. We find that tax enforcement led to a twenty-fold increase in conflicts between taxpayers and the state in municipalities in the high-tax region. This effect persists until the French Revolution, supporting the view that enforcing the salt tax incurred significant political costs. Finally, we document that the likelihood of conflict increases with tax differences between neighboring regions, which we use to derive an upper bound on the political costs of increased tax enforcement in this historical period.
Keywords: D74; H26; H39; K42; N43; 330; taxation; protest; conflict